A Critical Role for Mucosal-Associated Invariant T Cells as Regulators and Therapeutic Targets in Systemic Lupus Erythematosus - Murayama, Goh; Chiba, Asako; Suzuki, Hitoshi; Nomura, Atsushi; Mizuno, Tomohiro; Kuga, Taiga; Nakamura, Shinji; Amano, Hirofumi; Hirose, Sachiko; Yamaji, Ken; Suzuki, Yusuke; Tamura, Naoto; et al. (Frontiers in Immunology, 2019)
Mucosal-associated invariant T (MAIT) cells are a subset of innate-like lymphocytes that are restricted by major histocompatibility complex-related molecule 1 (MR1). In this study, we investigated the role of MAIT cells in the pathogenesis of lupus in FcγRIIb-/-Yaa mice, a spontaneous animal model of lupus. Using two approaches of MAIT cell deficiency, MR1 knockout animals and a newly synthesized inhibitory MR1 ligand, we demonstrate that MAIT cells augment the disease course of lupus by enhancing autoantibody production and tissue inflammation. MR1 deficiency reduced germinal center responses and T cell responses in these mice. Suppression of MAIT cell activation by the inhibitory MR1 ligand reduced autoantibody production and lupus nephritis in FcγRIIb-/-Yaa mice. MAIT cells directly enhanced autoantibody production by B cells in vitro. Our results indicate the contribution of MAIT cells to lupus pathology and the potential of these cells as novel therapeutic targets for autoimmune diseases such as lupus.